The continuum guide to successful teaching in higher education - Pons, Manuel M. (New York : Viva continuum edition, 2006)
This definitive resource covers every aspect of teaching in higher education. Particular emphasis is placed on the two main concerns facing professors in North America and the UK today; the growing emphasis on the quality of college teaching and, more specifically, the increasingly demanding nature of the profession, whereby lecturers are forced to teach more students on a greater number of courses. Pons' practical advice is supported throughout by research evidence
Includes references and index.
Keywords: College teaching; Pédagogie universitaire; Enseignement efficace